Comparative and International Legal Study on the Position of Irregular Migrants in the United Kingdom, Russia and South Africa: Issues of Their Internal Legal Capacity and Immigration Control Regimes - Leonidov, Ivan I. (2004)
PhDThe present thesis deals with the legal position of irregular migrants in the three receiving societies, i. e. Britain, Russia and South Africa. Irregular migrants are an exploited underclass enjoying very few, if any, entitlements in the host countries and so long as their numbers are substantial their status becomes problematic both for them and the receiving society. To deal with these challenges, I propose that immigration policies or regimes, directly or indirectly related to regulation of the irregular migrants' position (internal legal capacity) are too restrictive and discriminatory for the position of irregular migrants and do not constitute an effective means of immigration control. In order to test this hypothesis, a socio-legal analysis of irregular migrants' position is made in the following spheres: entry, residence, employment (including temporary labour migration policies) and social welfare. The position of asylum seekers constitutes an integral part of the present analysis. The research led to two general conclusions in relation to irregular migration. First of all, irregular migrants should be granted at least a limited internal juridical capacity in the countries of residence. Secondly, there should be a more liberal labour migration policy and more balanced approaches to the humanitarian needs of immigrants. These liberal solutions could nevertheless be combined with rigorous internal control